A time-motion analysis of Paralympic football for athletes with cerebral palsy - Boyd, C.; Barnes, C.; Eaves, S. J.; Morse, C. I.; Roach, N.; Williams, A. G. (International Journal of Sports Science & Coaching, 2016)
To investigate the soccer match-play work of players with cerebral palsy, 40 elite players were monitored for cardiovascular and locomotive demands of tournament match play. Using global positioning satellite and heart rate monitors, total distance travelled, distance travelled at high intensity and very high intensity (m); frequency of high intensity and very high intensity activity; heart rate. Disability classes C5/6, C7 and C8 were compared. The results showed C8 players covered the greatest distance. Frequency, contribution and maximum speed of high intensity and very high intensity activity was greater in C8. There was a progressive decline in distances covered in all classes across match quarters. C8 spent more time above 85% HRmax. No differences were observed between C5/6 and C7 classes. In conclusion, C8 players most notably perform best in very high intensity activity associated with game-defining moments. C5/6 and C7 players performed equitably. This study is the first to provide an insight for practitioners and coaches interested in the work rates in soccer for athletes with cerebral palsy. ABSTRACT FROM AUTHOR